The Independent Learning-Independent Campus Policy: Students’ Awareness of Mathematics Education - Benny Hendriana; Tri Wintolo Apoko; Windia Hadi; Isnaini Handayani; Supandi Supandi; Eka Nana (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study is to assess students' awareness of mathematics education in light of independent learning-independent campuses (ILIC). The phases of the survey research technique were used to conduct this research, and a questionnaire was used as the instrument for gathering data. All of the students studying mathematics at the private university served as the participants of the study. Winsteps and Rasch's model were used to examine the questionnaire data. The results from the Rasch model's processing are then analyzed based on the researcher's objectives. Findings: According to this study, 60.73 percent of students had a high level of awareness of the ILIC. 7.69 percent of students exhibited a low level of awareness of the ILIC, while 31.58 percent of students were still unaware of its existence. In conclusion, students' awareness of ILIC, which is run by the Republic of Indonesia's Ministry of education, culture, science, and technology, has to be improved.